Clinic front desk performance optimization using web-resource. Goal setting. - Kuropteva K. M. (Scientific research and developments of students, 2016)
This article deals with activity optimization process, illustrated by the example of the Severodvinsk Child Health Centre №1. It is reported that the medical record department's effectiveness can increase by creating an automized information system with an additional call registration module.
Keywords: информационная система; information system; вызов врача; педиатр; медицинский регистратор; general pedeatrician; medical record department